MENDESKRIPSIKAN PELAKSANAAN MODEL PEMBELAJARAN RADEC DENGAN PEMBELAJARAN JARAK JAUH BAGI SISWA KELAS SEKOLAH DASAR: MENDESKRIPSIKAN PELAKSANAAN MODEL PEMBELAJARAN RADEC DENGAN PEMBELAJARAN JARAK - Gustiayu Juita Harun; Arlina Yuza (Program Studi PGSD FKIP Universitas Bung Hatta, 2022)
Since the emergence of Covid in Indonesia, the education sector in Indonesia has experienced changes in learning activities. This makes the ministry think of various efforts so that learning activities can still be carried out and teachers think of a learning model that can help students achieve their goals optimally. The research was conducted for fifth graders at El Fitra Elementary School which aims to determine the implementation of the Radec learning model with distance learning for students. The results of this study indicate that the Radec model has a good effect on helping students learn in online learning. This can be seen from being active and students being able to explain answers to pre-learning questions. However, in distance learning, there are still students who do not heed the teacher's instructions to read and are actively involved in learning.